2010
DOI: 10.1016/s1878-6480(10)70243-3
|View full text |Cite
|
Sign up to set email alerts
|

241 Particularities of the epidemiology of lower-extremities peripheral artery disease in Central Africa

Abstract: International audienceBackgroundIn the western countries, a high prevalence of lower-extremities peripheral artery disease (LE-PAD) is reported in the elderly. The epidemiological transition in the developing countries might also involve this affection, but data regarding LE-PAD in Sub-Saharan Africa are unknown. We sought to determine the prevalence and risk factors for LE-PAD in the general elder population in 2 Sub-Saharan African countries: Congo and Central African Republic.MethodsWe performed 2 cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
1
1
Order By: Relevance
“…Population based studies have previously reported an association of PAD with female sex [33] and hypertension [34], which we have also shown in our study. In our clinic, the majority of the patients are of the female sex [35].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Population based studies have previously reported an association of PAD with female sex [33] and hypertension [34], which we have also shown in our study. In our clinic, the majority of the patients are of the female sex [35].…”
Section: Discussionsupporting
confidence: 90%
“…In the multivariable-adjusted analysis, we found that female sex, current high blood pressure, and use of glibenclamide were predictive of PAD. Population based studies have previously reported an association of PAD with female sex [ 33 ] and hypertension [ 34 ], which we have also shown in our study. In our clinic, the majority of the patients are of the female sex [ 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…Studies have also reported an association of PAD with hypertension 23 and in our study, although the prevalence of PAD was higher among clients with hypertension, there was no significant association between PAD and hypertension. In another multi-racial cross sectional study performed in Malaysia, Asia to determine the prevalence of ABI in 200 diabetic patients at a primary care setting, the overall prevalence of PAD was 16% in this diabetic population.…”
Section: Discussioncontrasting
confidence: 65%
“…Worldwide PAD prevalence varies between 4.5 to 57% and between 10 and 50% in an African population (1)(2)(3)(4). Smoking, diabetes mellitus, hypertension dyslipidaemia, age and genetic factors predispose to development of leg PAD (5).…”
Section: Introductionmentioning
confidence: 99%